Proximate and Mineral Composition of Roasted and Defatted Cashew Nut (Anarcadium occidentale) Flour - Segun, Omosuli Vincent; Tesleem, Ibrahim Adewale; Dare, Oloye; Rachael, Agbaje; Bolanle, Jude-Ojei (Pakistan Journal of Nutrition, 2009)
Cashew nut (Anarcadium occidentale) was roasted, defatted and processed into flour. The flour was evaluated for its physicochemical characteristics (Proximate and Minerals). The proximate composition (%) was as follows: moisture (5.52±0.2) ash (4.41±0.1), crude fat (34.95±0.2), crude protein (27.31±0.0) crude fibre (1.42±0.2) carbohydrate (by difference) 25.39 and energy (Kcal) (534.35). The result of the mineral composition (mg/100 g) showed that roasted and defatted cashew nut flour contains calcium (21.4±0.23) potassium (38.5±0.1) magnesium (36.4±0.3) Iron (0.8±0.1) Zinc (0.9±0.1), Sodium (22.6±0.2) Copper (0.4±0.1). It is obvious that the flour is a good source of energy, protein and minerals.